Effect of Ethanol Extract of Rosella Flower (Hibiscus sab- dariffa L.) on the Expression of Fibroblast Growth Factor-2 (FGF-2) and Matrix Metalloproteinase-1 (MMP-1) in the Healing Process of Incision Wounds in White Wistar Rats - Pratiwi, Ade Dwi; Siahaan, Jekson Martiar; Anto, Endy Juli (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: This study investigated the effect of rosella flower petal (Hibiscus sabdariffa L.) ethanol extract gel on incision wound healing in a rat model of diabetes mellitus. Wounds are skin disorders that can be caused by internal or external factors. The wound healing process involves various growth factors, including Fibroblast Growth Factor-2 (FGF-2) and Matrix Metalloproteinase-1 (MMP-1). Materials and Methods: This study used a posttest-only controlled group design with male Wistar rats as the research subjects. This study aimed to evaluate the effect of rosella flower petal ethanol extract gel on FGF-2 and MMP-1 levels, as well as collagen and fibroblast cell formation in the wound healing process. Results: Phytochemical screening results revealed the presence of flavonoids, alkaloids, saponins, phenols, and tannins in rosella extract. The results showed a significant difference (p<0.05) in FGF-2 levels between all research groups and significant difference (p<0.05) in MMP-1 levels. Conclusion: The group that received ethanol extract gel of rosella flower petals with a concentration of 12% showed a better increase in the formation of FGF-2, MMP-1, collagen, and fibroblast cells compared to the other groups
Keywords: Ethanol Extract Rosella Flower Petals; Incision Wounds; White rat; Wistar strain